Performance of Primary Fan in the Toguraci Underground Mine - Dea Natasa; Peter Eka Rosadi (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
The Toguraci Underground Mine of PT Nusa Halmahera Minerals (PT NHM) experienced a temporary production shutdown, resulting in the ventilation system operating below its original design conditions; Primary Fan T01 was operated at 60% of its maximum capacity (600 RPM out of 990 RPM). As mining operations resume under normal conditions, an evaluation of primary fan performance is required to ensure the ventilation system can meet operational airflow requirements. This study aims to evaluate the suitability of primary fan performance against underground airflow requirements and to determine the optimum primary fan operating configuration under normal conditions. A quantitative approach was employed through field measurements of pressure, airflow quantity, temperature, humidity, and air velocity, followed by analysis using fan affinity laws, factory performance curves, airflow requirement calculations, and configuration simulations. The results indicate that the actual airflow delivered by Primary Fan T01 was lower than the manufacturer's design performance, with a deviation of 27.89 m3/s. Under contingency conditions, the primary fan was still capable of supplying sufficient airflow; however, under normal operating conditions the actual airflow was insufficient, requiring a configuration adjustment. The optimum configuration was achieved by increasing the rotational speed of Primary Fan T01 to 900 RPM and operating two motors on Primary Fan T03, meeting the required airflow of 207.43 m3/s with a power demand of 640.74 kW.